足関節背屈制限と歩行速度の変化が歩行時の下肢関節角度と筋活動に与える影響 - 北谷, 亮輔; 大畑, 光司; 澁田, 紗央理 (日本基礎理学療法学雑誌, 2013)
Limited range of motion at the ankle joint is one of the main causes of genu recurvatum. The purpose of this study was to clarify the kinematic and electromyographic changes induced by limited ankle joint motion during gait.Eleven healthy subjects (21.5 ± 0.8 years old) participated in this study. An ankle-foot orthosis was used to limit the ankle dorsiflexion (DF) motion from 0 to 20 degree. The gait analysis was performed at 2, 3, 4, and 5 km/h on a treadmill. The joint angles and electromyographic signals on the right side of the lower limb were measured during gait. In addition, the degree of heel elevation during the stance phase, which is a kinematic change caused by limited DF motion, was measured.The knee angle extended significantly as DF motion was limited, whereas it flexed significantly as gait speed increased during loading response and single-limb stance phase. Rectus femoris and vastus medialis muscle activities increased significantly with increased gait speed during the same phases. Heel elevation significantly increased with limited ankle motion and increased gait speed during the stance phase.These results suggest that genu recurvatum is influenced by gait speed. With changes in knee angle, quadriceps muscles become more activated to support the weight in the flexed knee position.